WEAR AND HEAT-RESISTANT ALLOYS BASED ON COBALT - Кіндрачук, М.; Тісов, О. (Science-based technologies, 2010)
Current paper investigates tribotechnical properties of high temperature composite cobalt-based alloys The in-fluence of internal structure on their wear resistance was concidered. Article points on the possibility to use them as materias at GTE turbine blades manufacturing an restoration procedures.